A Class of Laguerre-Based Generalized Humbert Polynomials. (30th July 2021) - Batra, Saniya; Rai, Prakriti
Abstract : Several mathematicians have extensively investigated polynomials, their extensions, and their applications in various other research areas for a decade. Our paper aims to introduce another such polynomial, namely, Laguerre-based generalized Humbert polynomial, and investigate its properties. In particular, it derives elementary identities, recursive differential relations, additional symmetry identities, and implicit summation formulas.